PERTUMBUHAN DAN HASIL KEMBANG TELANG (Clitoria ternatea L.) PADA BERBAGAI KADAR AIR TANAH YANG DIBERIKAN PUPUK BIO-SLURRY DENGAN DOSIS BERBEDA - Arnawa I W.; I W. Suarna; I G. Mahardika (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2017)
This research is aimed to know the growth and yield of butterfly pea (Clitoria ternatea L.) at various level of water content and bio-slurry fertilizers. This research was conducted for 4 months at Tropical Forage Science Laboratory, Faculty of Animal Husbandry, Udayana University. The experiment design used a completely randomized design (CRD) in split plot pattern. Main factor or main plot is various level of water content: water content 60% (K1), 80% (K2), and 100% (K3) of field capacity, while sub factor or sub plot is level of fertilizer dosage: 0 ton ha-1 (D0), 10 ton ha-1 (D1), 20 ton ha-1 (D2), 30 ton ha-1(D3). The treatment repeated as much as 4 times. The variables observed in this study are growth and forage yield. The result of this research showed that giving various level of water content with different dosage bio-slurry fertilizer give significant effect (P<0,05) to growth and forage yield of butterfly pea (C. ternatea). There is no interaction between the treatment of level water content with the dosage of fertilizer to growth and the forage yield of butterfly pea (C. ternatea). Based on the result of the research, it can be concluded that the 80% (K2) level water content and 20 ton ha-1 (D2) fertilizer resulted in the best growth and forage yield of butterfly pea (C. ternatea). Keywords: growth and yield, butterfly pea, water content, bio-slurry.